Role of lipofibroblasts in alveolar regeneration after viral infection - Kiliaris, Georgios; Justus Liebig University Giessen (My University, 2025)
As of today, pneumonia induced ARDS has a very high mortality rate with effective treatments being extremely limited. One of the main features of ARDS is the presence of oedema in the airspace of the lung which happens because of the damage inflicted on the tight junctions of the alveolar epithelial cells resulting in the collapse of the alveoli. During homeostasis, it is already known that alveolar fibroblasts 1 (AF1) or lipofibroblasts, are in a very close proximity with the alveolar type 2 (AT2) cells providing them with lipid droplets and therefore supporting them with surfactant production. So, a strong communication between the mesenchyme (AF1 cells) and the alveolar epithelium (AT2 cells) is in effect during homeostatic conditions. Our bulk RNA sequencing data from the mesenchyme of the lung in mock and infected wild type mice (7- and 14-days post infection), showed that the differences in the transcriptomic profile of the 7 d.p.i. mice compared to the control were significant, and between the 14 d.p.i. mice and mock relatively similar, indicating that at 14 d.p.i. the lung was recovering. Importantly, when we looked at the top 100 upregulated genes between days 7 and 14, we noticed several genes associated with AF1 being upregulated 14 d.p.i.. The same genes were also significantly downregulated 7 d.p.i. compared to the mock mice. Following that, we performed a GSEA analysis for the AF1 signature in both day 7 and 14 and that confirmed the loss of AF1 signature 7 d.p.i. and its recovery at 14 d.p.i.. To follow the fate of AF1, we used the Fgf10CreERT2;tdTomatoflox line to lineage trace them and since we have previously shown that metformin can act on the AF1 and have a positive impact on the resolution of bleomycin induced fibrosis in mice, we used metformin as a therapeutic factor. Our data revealed that mice treated with metformin were doing better after infection with significantly less damage present on the lung. We could also observe the loss of the lineage after infection and its restoration after treatment with metformin with the AF1 regaining their lipogenic phenotype. Our single cell RNA sequencing data, also showed us that metformin was able to alter the transcriptomic profile of the lineage traced cells with pathways such as mTOR, cGMP- PKG and AMPK being upregulated and processes such as alveolar development and 59 morphogenesis being enriched. Our results were confirmed in our murine and human PCLS infection model with AF1 markers and, most importantly, AT1 and AT2 markers being upregulated after metformin treatment. Single cell RNA sequencing analysis on the SftpcCre-ERT2;tdTomatoflox lineage traced mice, a line that trace the fate of the AT2 cells, also showed that metformin can accelerate the differentiation of AT2 cells through ADIs to AT1 cells. Integrating the Fgf10Cre-ERT2;tdTomatoflox and SftpcCre-ERT2;tdTomatoflox single cell RNA sequencing data sets, gave us the opportunity to study the dynamics in the intercellular communication between AF1 and AT2. Thus, after performing a comprehensive CellChat analysis, we were able to identify GDF10 and HH as unique pathways of interaction between AF1 and AT2 after treatment with metformin. Quantitative PCR analysis on the murine and human PCLS infection models confirmed the upregulation of GDF10 after treatment with metformin. Also, treating murine PCLS with recombinant GDF10 after infection, showed upregulation of AT1 and AT2 markers further strengthening the idea that GDF10 is important for lung regeneration after influenza-induced lung injury. Importantly, when we studied the human lung cell atlas, we observed a significant downregulation of the AF1 signature and on the expression of GDF10 in the SARS- CoV-2 patients data compared with the donors. The downregulation of GDF10 was also confirmed when we performed in situ hybridization in three different IAV-induced ARDS patients compared to three different donors. With these data, we were able to show the relevance of our murine based results to the human pathological conditions.
Keywords: ddc:610